Venetoclax plus LDAC for newly diagnosed AML ineligible for intensive chemotherapy: a phase 3 randomized placebo-controlled trial - Wei, Andrew H; Montesinos, Pau; Ivanov, Vladimir; DiNardo, Courtney D; Novak, Jan; Laribi, Kamel; Kim, Inho; Stevens, Don A; Fiedler, Walter; Pagoni, Maria; Samoilova, Olga; Hu, Yu; et al. (Blood, 2020)
Effective treatment options are limited for patients with acute myeloid leukemia (AML) who cannot tolerate intensive chemotherapy. Adults age ≥18 years with newly diagnosed AML ineligible for intensive chemotherapy were enrolled in this international phase 3 randomized double-blind placebo-controlled trial. Patients (N = 211) were randomized 2:1 to venetoclax (n = 143) or placebo (n = 68) in 28-day cycles, plus low-dose cytarabine (LDAC) on days 1 to 10. Primary end point was overall survival (OS); secondary end points included response rate, transfusion independence, and event-free survival. Median age was 76 years (range, 36-93 years), 38% had secondary AML, and 20% had received prior hypomethylating agent treatment. Planned primary analysis showed a 25% reduction in risk of death with venetoclax plus LDAC vs LDAC alone (hazard ratio [HR], 0.75; 95% confidence interval [CI], 0.52-1.07; P = .11), although not statistically significant; median OS was 7.2 vs 4.1 months, respectively. Unplanned analysis with additional 6-month follow-up demonstrated median OS of 8.4 months for the venetoclax arm (HR, 0.70; 95% CI, 0.50-0.98; P = .04). Complete remission (CR) plus CR with incomplete blood count recovery rates were 48% and 13% for venetoclax plus LDAC and LDAC alone, respectively. Key grade ≥3 adverse events (venetoclax vs LDAC alone) were febrile neutropenia (32% vs 29%), neutropenia (47% vs 16%), and thrombocytopenia (45% vs 37%). Venetoclax plus LDAC demonstrates clinically meaningful improvement in remission rate and OS vs LDAC alone, with a manageable safety profile. Results confirm venetoclax plus LDAC as an important frontline treatment for AML patients unfit for intensive chemotherapy. This trial was registered at www.clinicaltrials.gov as #NCT03069352.
Keywords: Bridged Bicyclo Compounds, Heterocyclic; Leukemia, Myeloid, Acute; bicyklické sloučeniny heterocyklické; cytarabin; Humans; Cytarabine; lidé středního věku; Female; Aged; mutace; dospělí; protokoly protinádorové kombinované chemoterapie; sulfonamidy; výsledek terapie; senioři; lidé; Adult; indukce remise; ženské pohlaví; Kaplanův-Meierův odhad; Male; Middle Aged; Treatment Outcome; Antineoplastic Combined Chemotherapy Protocols; Remission Induction; Aged, 80 and over; senioři nad 80 let; Kaplan-Meier Estimate; Mutation; mužské pohlaví; akutní myeloidní leukemie; Sulfonamides